Adjuvant Therapy and Prognosticators of Survival in Head and Neck Mucosal Melanoma. (6th August 2021) - Abiri, Arash; Yasaka, Tyler M.; Lehrich, Brandon M.; Goshtasbi, Khodayar; Papagiannopoulos, Peter; Tajudeen, Bobby A.; St. John, Maie A.; Harris, Jeremy P.; Kuan, Edward C.
Abstract : Objectives/Hypothesis: To identify prognosticators and determine the efficacies of surgery with adjuvant radiotherapy (SR) and surgery with immunotherapy (SI) of head and neck mucosal melanoma (HNMM). Study Design: Retrospective database study. Methods: The 2004 to 2017 National Cancer Database was queried for HNMM patients. Cox proportional hazards and Kaplan‐Meier analyses evaluated prognosticators of mortality and survival benefits conferred by SR, SI, or surgery with adjuvant radiotherapy and immunotherapy (SRI). Logistic regression identified predictors of adjuvant radiotherapy or immunotherapy use. Results: Overall, 1, 910 cases (845 surgery, 802 SR, 51 SI, 101 SRI) were analyzed, with 50.3% females and an average age of 68.6 ± 13.8 years. SI was associated with greater overall survival (OS) than surgery (hazard ratio [HR] 0.672; P = .036). SI (HR 0.425; P = .024) and SRI (HR 0.594; P = .045) were associated with superior OS than SR. Older age (HR 1.607; P < .001), female sex (HR 0.757; P = .006), paranasal sinus localization (HR 1.648; P < .001), T4 classification (HR 1.443; P < .001), N1 classification (HR 2.310; P < .001), M1 classification (HR 3.357; P < .001), and positive surgical margins (HR 1.454; P < .001) were survival prognosticators. Adjuvant radiotherapy use was negatively correlated with older age, oral cavity localization, and M0 or T3 tumors (all P < .05). Adjuvant immunotherapy use was positively correlated with younger age and M1 tumors (all P < .05). Conclusions: Although SR did not confer survival benefits in HNMM patients, SI and SRI yielded greater OS than surgery alone. SRI was associated with superior survival outcomes than SR. Certain demographic and clinical factors were associated with increased mortality risk. Patient age and certain tumor characteristics were predictors of adjuvant radiotherapy or immunotherapy use. Level of Evidence: 4 Laryngoscope, 132:584–592, 2022